Nonmarital Sex Rituals on Mount Kemukus (Study of Legal Culture and Islamic Law Perspective) - Huda, Muhammad Chairul; Yusriyadi, Yusriyadi; Thohir, Mudjahirin; Miftahuddin, Miftahuddin; Iqdami, Muhammad Nazil (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
The legal construction in the Criminal Code (KUHP) and Islamic law the ban of extramarital sexual encounters, yet in Mount Kemukus, a different reality prevails. The formulation of the problems in this research are; first, what is the pattern of pilgrims' actions on Mount Kemukus? and second, what is the ideal of legal culture in Mount Kemukus? This study is from the perspective of legal culture and Islamic law. This paper examines the relationship between legal culture and Islamic law. This research is a field study employing a multidisciplinary socio-legal methodology. Observation and interviews were used to collect primary data, whilst a review of the literature was used to collect secondary data. This article combines social theory, legal theory, and Islamic legal theory to form an eclectic theory. This study found two general patterns, santri pilgrims and non-santri pilgrims, which represent the motivations, sources of belief, and patterns of pilgrims' actions; and (2) the ideal of legal culture in Mount Kemukus is to perform tawaṣul to Prince Samudro without performing non-marital sex rituals, and the law functions as a tool of social engineering for the benefit of society. The findings of this study suggest that in conditions of compulsion and despair, individuals seek justification for their actions even though they are against the social order. This research is useful for legal policies that regulate rituals and pilgrimages.